2005
DOI: 10.1292/jvms.67.121
|View full text |Cite
|
Sign up to set email alerts
|

Seminoma with Hyperesterogenemia in a Yorkshire Terrier

Abstract: ABSTRACT. A male 8-year-old Yorkshire Terrier dog with unilateral cryptorchism was presented for investigation of reduced appetite and multifocal alopecia. Abdominal sonography and radiography demonstrated abnormal enlargement of left testicle in abdominal cavity. Both of the retroperitoneal cryptorchid testicle and the other contralateral testicle were removed surgically. The concentrations of testosterone and estradiol in blood collected from the jugular vein and the two spermatic veins were evaluated and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
1
15
0
2
Order By: Relevance
“…Seminomas are usually documented in right testicle and can be found in solitary or multiple masses. They generally had pulpy consistency (4,9,10). Cut sections can be coincided with haemorragie and necrosis.…”
Section: Bir Köpekte Bilateral Diffuz Malign Seminomamentioning
confidence: 99%
See 2 more Smart Citations
“…Seminomas are usually documented in right testicle and can be found in solitary or multiple masses. They generally had pulpy consistency (4,9,10). Cut sections can be coincided with haemorragie and necrosis.…”
Section: Bir Köpekte Bilateral Diffuz Malign Seminomamentioning
confidence: 99%
“…Seminomas, sertoli cell tumors and Leydig cell tumors are most encountered among primary testicle tumors according to World Health Organization (WHO) (1,4,6,7,9). And histologically evaluated mainly in two types (tubular and diffuse type).…”
Section: Bir Köpekte Bilateral Diffuz Malign Seminomamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the measurement of excessive intralesional oestradiol concentration can assist with the confirmation of the SCT metastasis (Gopinath et al 2009). Although SCTs are the most common testicular neoplasia to cause hyperoestrogenaemia, others have been reported, including a case of seminoma in a Yorkshire terrier (Kim and Kim 2005).…”
mentioning
confidence: 99%
“…Bu tümöre ayrıca aygır (9), koç, teke ve boğalar ile diğer türlerde de az oranda rastlanır (4). Kriptorşidizm seminom oluşu-munda predispoze bir faktördür.…”
unclassified